PRODUKSI JAGUNG (Zea mays saccharata L.,) BERBASIS KOMPOS JERAMI DAN PUPUK ORGANIK CAIR DAUN GAMAL - Setiaaji, Amalia S.; Polii-Mandang, J. Sh.; Paulus, Jeanne M. (EUGENIA, 2017)
ABSTRACT   This study aims to assess the dose straw compost and liquid organic fertilizer spraying frequency Gliricidia leaves right on the growth and production of corn (Zea mays saccharata L.,) as well as the interaction between them. The treatment is carried out is designed in a factorial experiment in a randomized block design (RDB), which factor straw compost consists of 3 dose levels:         10 ton ha-1, 15 ton ha-1 and 20 ton ha-1, while the frequency factor spraying liquid organic fertilizer gliricidia leaves consists of 3 levels frequency: 5 days, 10 days and 15 days using three replications. The results showed that the frequency of spraying a liquid organic fertilizer Gliricidia leaves single influence on the diameter of the stem of the plant. Interaction straw compost and liquid organic fertilizer spraying frequency Gliricidia leaves no real effect on the growth and production of corn. Dose straw compost 10 tons ha-1 and the frequency of spraying liquid organic fertilizer Gliricidia leaves 15 days to produce the best production is 8.21 tons ha-1. Keywords: straw compost, gliricidia leaves liquid organic fertilizer, corn